A Study Of Judo Sports Teaching And Learning Problems In Elective Subjects For University Hebei Province - Xiaoqing, Huo; Duangkam, jakrin; Khantiyu, Yodkhwan; Hengsuko, Ekasak (Journal of Roi Kaensarn Academi, 2024)
The purposes of this research was to: A Study of judo sports teaching and learning problems in elective subjects in university Hebei province. The samples were selected from 4 general colleges and universities in Hebei Province using 29 judo teachers and 800 judo elective students by simple random sampling. The research instrument used was a 2 questionnaire with a reliability at 0.81and 0.92 respectively. The statistical tools used for data analysis were mean and standard deviation. The results indicate that: 1) Teachers research findings: The position of teacher may meet the needs of teaching, however due to inconsistencies in concentration, teaching locations and facilities need to be improved further. There needs to be more specialized judo teaching materials. The preparation of lesson plans meets the national requirements, but the class time does not meet the national requirements. 2) Student research findings: The students of judo elective subjects have a reasonable degree of fondness and learning effect, contributing to judo benign development. However, the students think that due to the judo sports teaching hours are small, the teaching method is outdated, the teaching assessment and evaluation of the main factors affecting the interest in learning, but also the students on the content of the teaching set up and the form of teaching organization is also unsatisfactory.